Stability of anti-reflection coatings via the self-assembly encapsulation of silica nanoparticles by diazo-resins. (December 2015) - Metzman, Jonathan S.; Ridley, Jason I.; Khalifa, Moataz B.; Heflin, James R.
Abstract: A modified silica nanoparticle (MSNP) solution was formed by the encapsulation of negatively charged silica nanoparticles by the UV-crosslinkable polycation oligomer diazo-resin (DAR). Appropriate DAR encapsulation concentrations were determined by use of zeta-potential and dynamic light scattering measurements. The MSNPs were used in conjunction with poly(styrene sulfonate) (PSS) to grow homogenous ionic self-assembled multilayer anti-reflection coatings. Stability was induced within the films by the exposure of UV-irradiation that allowed for crosslinking of the DAR and PSS. The films were characterized by UV/vis/IR spectroscopy and field emission scanning electron microscopy. The transmission and reflection levels were >98.5% and <0.05%, respectively. The refractive indices resided in the 1.25–1.26 range. The solvent stability was tested by sonication of the films in a ternary solvent (H2 O/DMF/ZnCl2 3:5:2 w/w/w). Highlights: Silica nanoparticles were encapsulated by diazo-resin in solution. Anti-reflection films were grown with the coated nanoparticles and PSS solution. The films exhibited excellent anti-reflection and homogeneity. After UV irradiation, crosslinking occurred between the diazo-resin and PSS. Solvent stability was demonstrated using a ternary solvent.